The Mediating Role of Protestant Work Ethic in The Relationship Between Organizational Culture, Transformational Leadership, and Personality on Teacher Job Performance - Nainggolan, Rinto Rain Barry (Universitas Dharma Wacana, 2024)
This study examines the mediating role of Protestant Work Ethic in the relationships between Organizational Culture, Transformational Leadership, and Personality on Teacher Job Performance in private Christian elementary schools in Banten Province. A quantitative survey involved 236 teachers as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with WarpPLS 7.0. The results indicate that Organizational Culture positively influences Protestant Work Ethic, while Transformational Leadership has a negative impact. Personality does not significantly affect Protestant Work Ethic. Protestant Work Ethic significantly enhances Teacher Job Performance. Organizational Culture and Personality directly contribute to Teacher Job Performance, whereas Transformational Leadership shows no significant direct impact. Mediation analysis reveals that Protestant Work Ethic partially mediates the relationships between Organizational Culture and Teacher Job Performance, as well as between Personality and Teacher Job Performance, but not between Transformational Leadership and Teacher Job Performance. This study concludes that Organizational Culture and Personality are key factors in improving Teacher Job Performance, with Protestant Work Ethic serving as a significant mediator. The findings emphasize the importance of cultivating a positive organizational culture and developing personal competencies to enhance Teacher Job Performance.